Analisis pemahaman konsep dan kemampuan komunikasi matematis siswa dengan strategi pembelajaran think-talk-write - Dian Ika Lestari; Nurdalilah Nurdalilah (Mahesa Research Center, 2023)
This study aims determine results of tests of conceptual understanding and communicatio skills with the TTW learning strategy conducted in class VIII of MTs Al Ikhlas Beringin Private. In this study, researcher used a qualitative descriptive type of research. In this study, data was collected by administering tests, by distributing test tests in the form of essay questions on cubes and blocks to 30 students in class 8-B of Al Ikhlas Beringin Private MTs in even semester of the school year. 2022/2023. After that, the results of each student's answer were classified for each indicator in understanding the concept and mathematical communication ability to be achieved as well as being used as a sample consisting of 6 students from the concept understanding test and 6 students from the student's mathematical communication ability test. The assessment is carried out by means of reduction, presentation of data and drawing conclusions. From the results of the analysis obtained, it can be concluded that the TTW learning strategy is carried out in class 8 MTs Al Ikhlas Beringin has a good effect because the average student score on the test of understanding concepts and students' mathematical communication skills is quite good.